Impact of antegrade enema initiation on healthcare utilization in pediatric patients: A population‐based cohort study. Issue 3 (15th November 2022) - Gould, Michelle J.; Marcon, Margaret A.; Nguyen, Geoffrey C.; Benchimol, Eric I.; Moineddin, Rahim; Swayze, Sarah; Kopp, Alexander; Ratcliffe, Elyanne M.; Merritt, Neil; Davidson, Jacob; Langer, Jacob C.; Mistry, Niraj; et al.
Abstract: Background: When constipation is refractory to first‐line interventions, antegrade enema use may be considered. We aimed to assess the impact of this intervention on healthcare utilization. Methods: We conducted a population‐based, quasi‐experimental study with pre–post comparison of the intervention group and a non‐equivalent control group using linked clinical and health administrative data from Ontario, Canada. Subjects included children (0–18 years) who underwent antegrade enema initiation from 2007 to 2020 and matched controls (4:1) from the general population. To assess the change in healthcare utilization following antegrade enema initiation, we used negative binomial generalized estimating equations with covariates selected a priori. Key Results: One hundred thirty‐eight subjects met eligibility criteria (appendicostomy = 55 (39.9%); cecostomy tube = 83 (60.1%)) and were matched to 550 controls. There was no significant difference in the change in the rate of hospitalizations (rate ratio (RR) 1.05, 95% confidence interval (CI) 0.35–1.75), outpatient visits (RR 1.05, 95% CI 0.91–1.18), or same‐day surgical procedures (RR 1.51, 95% CI 0.60–2.43) across cases in 2 years following antegrade enema initiation compared with controls. Cases had an increased rate of emergency department (ED) visits, which was not observed in controls (RR 1.52, 95% CI 1.11–1.79), driven in part by device‐related complications. Conclusions and Inferences: Understanding healthcare utilization patterns following antegrade enema initiation allows for effective health system planning and aids medical decision‐making. The observed increase in ED visits for device‐related complications speaks to the need to improve preventive management to help mitigate emergency care after initiation of antegrade enemas. Abstract : Following antegrade enema initiation in children, healthcare utilization remains stable for most forms of care, although emergency department care increased, in part secondary to device‐related visits.